Juridical historiography and local autonomies in the Italy’s contemporary age - Stanco, Gianfranco (Universidad Nacional del Litoral, 2015)
This essay aims at studying the interpretations made by the current juridical historiography in relation with the Italian Cities’ Statutory Law, as traditionally conceived during the Middle and Modern Ages, also taking into account the fact that the Statutory Law is important for the existing Italian constitutional system.